Description of postpartum blues in postpartum mothers - Mayangsari, Dewi; Yenik Retnowati; Sa’adah Mujahidah (Link Journal of Mental Health, 2024)
Postpartum blues is a temporary mental mood disorder. This phase will occur in mothers after giving birth, which is caused by psychological changes in the mother and emotional changes in a woman after giving birth. Efforts to prevent postpartum blues in postpartum mothers are through educational methods, one of which is using the media. Objective: To determine the level of postpartum blues in postpartum mothers before and after being given education through booklets and videos. Method: This quantitative research uses a quasi-experiment method with a two-group pretest-posttest research design. The respondents were 40 postpartum mothers from 2 intervention groups, and probability sampling was used using a simple random sampling method. instrument using a questionnaire Edinburgh Post-natal Depression Scale. Univariate analysis uses central tendency data (mean, median, standard deviation). Results. Rate of postpartum blues in postpartum mothers. The mean rank value shows that the mean value for the video media group is greater than the booklet group, so it is concluded that the mental health education video media group is more effective than the booklet group.